If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -5 = 8x + 13 Reorder the terms: -5 + 12x = 8x + 13 Reorder the terms: -5 + 12x = 13 + 8x Solving -5 + 12x = 13 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -5 + 12x + -8x = 13 + 8x + -8x Combine like terms: 12x + -8x = 4x -5 + 4x = 13 + 8x + -8x Combine like terms: 8x + -8x = 0 -5 + 4x = 13 + 0 -5 + 4x = 13 Add '5' to each side of the equation. -5 + 5 + 4x = 13 + 5 Combine like terms: -5 + 5 = 0 0 + 4x = 13 + 5 4x = 13 + 5 Combine like terms: 13 + 5 = 18 4x = 18 Divide each side by '4'. x = 4.5 Simplifying x = 4.5
| 5-(3x+2.5)=1 | | x^2+x=183 | | X^2+8x-y=0 | | 126/567= | | 7x-5=5x+10 | | 7/9*18/63= | | a*((64-2a)/2) | | 7/9*18/63 | | a^2-b^2=1000 | | a^2+b^2=1000 | | (X-3)2=14-2x | | 4x-12=54-4x | | ctg(x)=0 | | 0=ctg(0.5x)-1 | | 4cosx+5sinx=6 | | X^2y+y^3=0 | | 27x^2-27x=0 | | z^2-(3-i)z+4-3i=0 | | 3(x-15)=18 | | (D^3+D^2-8D-12)y=0 | | (10x+6)+(12-4x)=0 | | 3x-(5x+10)=6 | | 2^x*(16-2^3x/8)=0 | | 5(r-1)=2(1-r) | | 5+2=310 | | 3cos^2(x)-8cos(x)+4=0 | | 0.60*x=96 | | 4x^2+3x+7x^2-x-5x^2= | | 4-4(k-5)=2(2-k)6 | | 6(0)-6y=12 | | x*0.1=200 | | y/4x20/x |